2013
DOI: 10.1190/geo2012-0445.1
|View full text |Cite
|
Sign up to set email alerts
|

Background resistivity model from seismic velocities

Abstract: We developed a methodology to estimate resistivities from seismic velocities. We applied known methods, including rock physics, depth trends, structural information, and uncertainty analysis. The result is the range of background resistivity models that is consistent with the known seismic velocities. We successfully tested the methodology with real data from the North Sea. These 2D or 3D background resistivity models yield a detailed insight into the background resistivity, and they are a powerful tool for fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(14 citation statements)
references
References 29 publications
0
14
0
Order By: Relevance
“…Faust, 1953;Brito dos Santos et al, 1988;Hacikoylu et al, 2006;Werthmüller et al, 2013). In Hontomín, the log data of the GW1 and the H4 wells were used to derive resistivity-velocity relationships for the subsurface and compute a 3-D velocity model of the site, using the 3-D resistivity model as a reference.…”
Section: Resistivity-velocity Relationshipsmentioning
confidence: 99%
“…Faust, 1953;Brito dos Santos et al, 1988;Hacikoylu et al, 2006;Werthmüller et al, 2013). In Hontomín, the log data of the GW1 and the H4 wells were used to derive resistivity-velocity relationships for the subsurface and compute a 3-D velocity model of the site, using the 3-D resistivity model as a reference.…”
Section: Resistivity-velocity Relationshipsmentioning
confidence: 99%
“…Resistivity-velocity relationships have been used to calculate one physical parameter as a function of the other in numerous works (e.g. Faust, 1953;Brito dos Santos et al, 1988;Hacikoylu et al, 2006;Werthmüller et al, 2013). In Hontomín, the log data of the GW1 and the H4 wells were used to derive resistivity-velocity relationships for the subsurface and compute a 3-D velocity model of the site, using the 3-D resistivity model as a reference.…”
Section: Resistivity-velocity Relationshipsmentioning
confidence: 99%
“…Successful CO 2 storage sites include a complete characterization, dedicated to understanding the characteristics of the subsurface as well as ensuring the suitability, safety, and security of the site (e.g. Chadwick et al, 2004;Förster et al, 2006;White, 2013). The selection of Hontomín as a pilot CO 2 storage site motivated a multidisciplinary characterization of the area, aimed to unravel the main characteristics of the subsurface structures.…”
Section: Introductionmentioning
confidence: 99%
“…Primary applications of such cross-property relationship include filling in data gaps when one property is more readily available than the other. Advanced uses of such relationship include the input of a priori information to reduce ambiguity in the inversion process (Mukerji et al 2009;Werthmu¨ller et al 2013). (1953) has shown that both resistivity and velocity behave similarly with increasing depth.…”
Section: Background Resistivitymentioning
confidence: 99%
“…A second widely used alternative is the construction of the resistivity cube based on a velocity-porosity-resistivity petrophysical models available in the literature (Hashin & Shtrikman 1962;Hermance 1979;Werthmu¨ller et al 2013).…”
Section: Model Building Workflowmentioning
confidence: 99%